Changes in Gut Microbiota Prior to Influenza A Virus Infection Do Not Affect Immune Responses in Pups or Juvenile Mice - Fuglsang, Eva; Pizzolla, Angela; Krych, Lukasz; Nielsen, Dennis S.; Brooks, Andrew G.; Frøkiær, Hanne; Reading, Patrick C. (Frontiers in Cellular and Infection Microbiology, 2018)
Previous studies demonstrated that oral antibiotic (ABX) treatment prior to and during influenza A virus (IAV) infection of adult mice profoundly altered gut microbiota (GM) and was associated with increased susceptibility and impaired immunity to IAV. We examined the impact of ABX during critical times relevant to the establishment of GM in early life (using perinatal treatment of neonates and direct treatment of juvenile mice) and asked whether cessation of ABX treatment in early life had lasting effects on GM composition and anti-IAV immunity. ABX treatment significantly changed GM composition in juvenile mice and in ABX-treated dams. However, if ABX treatment ceased at the time of infection, neither neonates nor juvenile mice showed enhanced susceptibility to IAV, nor were major differences detected in cellular and humoral adaptive antiviral immunity. Thus, while ABX treatment alters GM diversity in early life, cessation and subsequent re-colonization correlates with effective immunity against IAV.